Fanon's dialectic of experience - Sekyi-Otu, Ato (Harvard University Press, 1996)
In this reinterpretation of Franz Fanon, Ato Sekyi-Otu ensures the reader's awareness of the formal complexity of Fanon's work. Fanon advocated national liberation and resistance to colonial power in his books, such as "Black Skin, White Masks".